SIMULASI NUMERIK DISTRIBUSI POLUSI UDARA DALAM RUANGAN - Bowo Yuli Prasetyo; Arda Rahardja Lukitobudi; Ade Suryatman Margana (Jurnal Teknologi Terapan, 2022)
The kitchen is a vital area that provides energy sources through food processing for residences. However, the cooking process can also produce pollutants that are harmful to the body. This study aims to investigate the concentration and distribution of contaminants (CO and CO2) generated from the kitchen to all rooms in the house. In addition, Air temperature and velocity are investigated to observe their relationship with the distribution of pollutants. The investigation procedure utilizes a numerical simulation of a dwelling with two different ventilation cases. The simulation results show no significant difference in air velocity between the two cases. While the addition of natural ventilation in the kitchen area can reduce CO and CO2 concentrations throughout the room by 25.8% and 24.9%, respectively. On the other hand, the indoor air temperature can also be reduced by 4.9% with the same treatment. In conclusion, the addition of a window in the kitchen area has a significant impact on reducing temperature and pollutant concentrations all over the room.